2016
DOI: 10.1016/j.cell.2016.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Bone and Muscle Endocrine Functions: Unexpected Paradigms of Inter-organ Communication

Abstract: Most physiological functions originate with the communication between organs. Mouse genetics has revived this holistic view of physiology through the identification of inter-organ communications that are unanticipated, functionally important and would have been difficult to uncover otherwise. This review highlights this point by showing how two tissues usually not seen as endocrine ones, bone and striated muscles, influence in a significant manner several physiological processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
176
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(186 citation statements)
references
References 61 publications
0
176
0
10
Order By: Relevance
“…The growing number of functions ascribed to osteocalcin (Karsenty and Olson, 2016) raises the question of whether the circulating levels of this hormone change in various physiological situations. This analysis revealed that a single bout of endurance aerobic-based exercise (40 minutes run on a treadmill at 30cm/s, 80% VO 2 max, thereafter referred to as exercise) increased circulating osteocalcin levels of total and undercarboxylated and bioactive two-fold in 3 month-old wild-type (WT) mice while at same time the circulating levels of insulin decreased.…”
Section: Regulation Of Osteocalcin By Exercise and Agementioning
confidence: 99%
“…The growing number of functions ascribed to osteocalcin (Karsenty and Olson, 2016) raises the question of whether the circulating levels of this hormone change in various physiological situations. This analysis revealed that a single bout of endurance aerobic-based exercise (40 minutes run on a treadmill at 30cm/s, 80% VO 2 max, thereafter referred to as exercise) increased circulating osteocalcin levels of total and undercarboxylated and bioactive two-fold in 3 month-old wild-type (WT) mice while at same time the circulating levels of insulin decreased.…”
Section: Regulation Of Osteocalcin By Exercise and Agementioning
confidence: 99%
“…Almost a century later, subsequent biological techniques have allowed bone and skeletal muscle, previously designated as nonendocrine organs, to be revealed as having endocrine functions (Karsenty and Olson, 2016). Karsenty and Olson (Karsenty and Olson, 2016) prognosticated, ''It is also likely that many more functionally important inter-organ communications and new physiologies remain to be discovered.'' The understanding of exercise physiology also had an early milestone when 1922 Noble Prize in Medicine winner A.V.…”
mentioning
confidence: 99%
“…For example, Banting and MacLeod won the 1923 Noble Prize in Medicine for their discovery of insulin being secreted from the pancreas and increasing glucose uptake in peripheral tissues (Banting et al, 1922). Almost a century later, subsequent biological techniques have allowed bone and skeletal muscle, previously designated as nonendocrine organs, to be revealed as having endocrine functions (Karsenty and Olson, 2016). Karsenty and Olson (Karsenty and Olson, 2016) prognosticated, ''It is also likely that many more functionally important inter-organ communications and new physiologies remain to be discovered.''…”
mentioning
confidence: 99%
“…The second molecule secreted by the bone is Ocn, a small peptide (46 amino acid-long in mice) synthetized by osteoblasts, which can be Îł-carboxylated on 3 glutamic acid residues [18,23,77,78]. Ocn is the most abundant non-collagenous protein of the bone ECM and can also be found in the general circulation.…”
Section: Bone As An Endocrine Organmentioning
confidence: 99%